Fungicide resistance and parasexual recombination in pseudocercosporella herpotrichoides - Hocart, Mark J. (1987)
A detailed investigation of benzimidazole resistance in field isolates and laboratory mutants of Pseudocercosporella herpotrichoides resulted in the description of four major resistance catagories, based on the sensitivity of isolates to carbendazim: high-level (MIC - >1000 pM), intermediate-level (MIC - 50 - 200 pM), low-level (MIC - 10 - 20 pM) and sensitive (MIC - 0.6 - 2.5 pM). Cross-resistance to other benzimidazole compounds, including thiabendazole, was observed in all cases, although the level of resistance to thiabendazole was not directly related to the level of resistance to carbendazim.